Life in the Desert Leads to Improvements at El Paso Water's Kay Bailey Hutchison Inland Desalination Plant. Issue 12 (4th December 2020) - Campos, Isaac; Guemez, Sarah; Arevalo, Jorge; Brown, Doug; Trejo, Gilbert
Abstract : After more than 10 years of operation, a Texas desalination plant could no longer produce blended finished water at its design capacity. New membranes were selected after a comprehensive evaluation process, and the facility was retrofitted with interstage booster pumps to operate under a variety of potential feedwater conditions.